Bacterial encapsulins as orthogonal compartments for mammalian cell engineering - Felix Sigmund (Nature Portfolio, 2018)
Artificial compartments have been expressed in prokaryotes and yeast, but similar capabilities have been missing for mammalian cell engineering. Here the authors use bacterial encapsulins to engineer genetically controlled multifunctional orthogonal compartments in mammalian cells.